IDENTIFICATION OF LOCAL FEED POTENTIAL IN BALI CATTLE BREEDING AREA IN KONAWE SELATAN REGENCY - Abadi, Musram; Nafiu, La Ode; Nasiu, Firman; Kurniawan, Widhi (Pascasarjana Universitas Sulawesi Tenggara, 2021)
This study was aimed to identify and inventory the availability potentiation of local feed in the South Konawe Bali Cattle Development Area. The material and methods in this study were types of Forage and agricultural waste that potential as animal feed sources. This research was conducted in 2018 in Tinanggea, Palangga, Buke, and Baito Districts, South Konawe Region. Local Forage was feed material that used for the development of cattle in the South Konawe District. The forage potential was calculated based on the feed production of ingredients according to the harvested area and expressed in dry matter (BK). The Forage and agricultural waste types in Konawe Selatan Regency were a) Forage feed, among others; Pennisetum purpureum (Elephant Grass), Apluda mutica (Field grass), Acconopus compresses (pait grass), Cenchrus salaries (foxtail grass), Chrisopogon articulates (Needlegrass); b) Agricultural crop agricultural waste, among others; Rice Straw, Corn straw, Cassava leaves, Sweet potato leaves, Peanut straw, and Soybean straw. The results showed that the production of Forage in South Konawe Bali Cattle Development Area was dominated by field grass (Apluda mutica), namely (a) Tinanggea Subdistrict as much as 23,706.67 tons/year (b) Palangga District as much as 4,128.72 tons/year; (c) Baito Subdistrict as much as 8,077.26 tons/year, and (d) Buke SubDistrict as much as 10,712.95 tons/year. Whereas food crop agricultural waste was rice straw feed namely (1) Tinanggea Subdistrict as much as 3,272,780 BK/kg/year; (2) Palangga District as much as 2,982,875 BK/kg/year; (3) Baito Subdistrict as much as 2,756,250 BK/kg/year and (4) Buke Subdistrict with 945,000 BK/kg/year, while corn straw, peanut straw, and cassava leaves cannot be determined.